2016
DOI: 10.1093/ijnp/pyw036
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mineralocorticoid and Glucocorticoid Receptor Antagonism on Autobiographical Memory Recall and Amygdala Response to Implicit Emotional Stimuli

Abstract: Background:Acutely elevated cortisol levels in healthy humans impair autobiographical memory recall and alter hemodynamic responses of the amygdala to emotionally valenced stimuli. It is hypothesized that the effects of the cortisol on cognition are influenced by the ratio of mineralocorticoid receptor to glucocorticoid receptor occupation. The current study examined the effects of acutely blocking mineralocorticoid receptors and glucocorticoid receptors separately on 2 processes known to be affected by alteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 53 publications
0
19
1
Order By: Relevance
“…Previous neuroimaging experiments have provided evidence that high levels of exogenous GCs, mimicking stress-associated states, alter both the neural processing in response to emotional or cognitive stimulation and the resting state functional connectivity (7)(8)(9)(10)(11)(12)(13)(14). These studies suggest a specific role for MRs in some of these stress-related changes in both neural processing and functional connectivity (15,16), while MR or GC receptor antagonism impacts the amygdala-dependent processing of emotional faces (77). Our study findings now provide evidence that even in the absence of a stressful stimulus, the ultradian GC rhythm is critical in regulating neural dynamics and, consequently, behavioral and cognitive phenotypes.…”
Section: Discussionmentioning
confidence: 95%
“…Previous neuroimaging experiments have provided evidence that high levels of exogenous GCs, mimicking stress-associated states, alter both the neural processing in response to emotional or cognitive stimulation and the resting state functional connectivity (7)(8)(9)(10)(11)(12)(13)(14). These studies suggest a specific role for MRs in some of these stress-related changes in both neural processing and functional connectivity (15,16), while MR or GC receptor antagonism impacts the amygdala-dependent processing of emotional faces (77). Our study findings now provide evidence that even in the absence of a stressful stimulus, the ultradian GC rhythm is critical in regulating neural dynamics and, consequently, behavioral and cognitive phenotypes.…”
Section: Discussionmentioning
confidence: 95%
“…These differential effects may be explained by differences in basal cortisol between different groups and also between people within a diagnostic group, as well as individual differences in the reception of cortisol within the brain, particularly in areas of the brain such as the hippocampus [37]. Indeed, administration of a glucocorticoid receptor antagonist to healthy participants, thereby reducing the occupation of these receptors by cortisol, has been found to lead to significant improvements in specificity relative to a placebo [69]. No study has yet examined the neural mechanism by which cortisol influences specific memory retrieval.…”
Section: The Neuroendocrinology Of Memory Specificitymentioning
confidence: 99%
“…Although earlier studies found no relation between MR functioning and perspective taking (Wingenfeld et al 2014 ), or even diminished perspective taking (Wingenfeld et al 2016 ), higher MR functioning after pharmacological stimulation resulted in enhanced empathic concern (Wingenfeld et al 2014 ) in clinically depressed adults. Moreover, in healthy subjects increased emotion processing has been reported after pharmacological stimulation (Schultebraucks et al 2016 ), and diminished emotion processing after pharmacological inhibition of MR functioning (Young et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%